1999
DOI: 10.1177/0261927x99018004002
|View full text |Cite
|
Sign up to set email alerts
|

Characterological and Behavioral Blame in Conversations about Female and Male Rape

Abstract: This study investigated the spontaneous occurrence of characterological and behavioral blame in talk about rape. Although participants are willing to attribute both types of blame to rape survivors when prompted to do so by preexisting categories on questionnaires, little is known about the naturalistic aspect of these concepts as they might occur during the course of conversation. The present study also examined how participant and survivor gender influence these attributions. Findings showed that observers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 37 publications
3
52
0
2
Order By: Relevance
“…With' respect to the latter, a substantial body of work has shown that observers attribute both characterological and behavioural blame to rape survivors and that some differences in blaming the victim were found between men and women observers (e.g. Anderson 1999). Such research could usefully inform future changes.…”
Section: Lea Et Almentioning
confidence: 99%
“…With' respect to the latter, a substantial body of work has shown that observers attribute both characterological and behavioural blame to rape survivors and that some differences in blaming the victim were found between men and women observers (e.g. Anderson 1999). Such research could usefully inform future changes.…”
Section: Lea Et Almentioning
confidence: 99%
“…In direct comparisons with judgements about female victims, studies on social reactions to male victims have shown that male rape victims are frequently judged as negatively or even more so than female victims (Whatley & Riggio. 1993;Struckman-Johnson & Struckman-Johnson, 1992;Smith, Pine & Hawley, 1988) although several studies have shown the opposite effect (Anderson, 1999, McCaul, Veltum, Boyechko & Crawford, 1990Schneider, Soh-Chiew Ee and Aronson, 1994). A frequent assumption is that a man could or should have been able to fight off his attacker (Perrott & Webber, 1996).…”
Section: Introductionmentioning
confidence: 98%
“…Although several factors appear to influence responses to male rape victims such as sexuality of the victim (Anderson, 2004;Mitchell et al, 1999;White & Kurpius, 2002;Bunting & Reeves, 1983) where a homosexual victim is blamed more for being raped than a heterosexual victim, one of the most frequently observed influences of judgements of male victims is participant gender. Men appear to be not only more punitive of female rape victims than women (Ward, 1995) but of male rape victims as well (Anderson, 1999;Anderson & Lyons, 2005;Struckman-Johnson & Struckman-ATTITUDES TOWARD RAPE 4 Johnson, 1992;Smith, Pine & Hawley, 1988;Mitchell et al, 1999;Whatley & Riggio, 1993). …”
Section: Introductionmentioning
confidence: 99%
“…Although researchers have long attempted to change negative perceptions of rape victims, these judgements continue to pervade both individual and institutional settings (Anderson, 1999;Ward, 1995). There is much evidence to suggest that despite years of campaigning, debate and education about their deleterious effects, misconceptions about rape and negative social responses to victims such as attributions of blame are still a common part of the rape victim's experience following disclosures of sexual violence to social network members.…”
Section: Introductionmentioning
confidence: 99%
“…We speculate that the victim may be attributed less blame by individuals if they observe that the victim is already The present study also examines male, as well as female rape. A small but growing literature on male rape has recently appeared (Anderson, 1999;Anderson, Beattie & Spencer, 2001;Isely & Gehrenbeck-Shim, 1997;Kaufman, DiVasto, Jackson, Voorhees & Christy, 1980;Mitchell, Hirschman & Nagayama Hall, 1999), representing a shift in focus from solely female to male rape, which can be attributed to the increasing public realisation that men can also be victims of rape. Until recently, it has generally been assumed by researchers and the lay population that male rape is rare, primarily occurring in incarcerated settings (Donnelly & Kenyon, 1996;Stermac, Sheridan, Davidson & Dunn, 1996;Struckman-Johnson & StruckmanJohnson, 1992;Whatley & Riggio, 1993).…”
Section: Introductionmentioning
confidence: 99%